Interpretacje cudów Jezusa - Antoni Paciorek (Vox Patrum, 2008)
The author presents two directions of interpreting the Biblical relations of miracles which are represented by great figures of the past, namely St. Augustin and St. Thomas, as well as two directions which clearly marked their existence in our contemporary times. These are the interpretation based on depth psychology (Drewermann) and the interpretation of miracles as images and signs of hope (Theissen, Langner, Metz).